Changes in the Proteome of Xylem Sap in Brassica oleracea in Response to Fusarium oxysporum Stress - Pu, Zijing; Ino, Yoko; Kimura, Yayoi; Tago, Asumi; Shimizu, Motoki; Natsume, Satoshi; Sano, Yoshitaka; Fujimoto, Ryo; Kaneko, Kentaro; Shea, Daniel J.; Fukai, Eigo; Fuji, Shin-Ichi; et al. (Frontiers in Plant Science, 2016)
Fusarium oxysporum f. sp. conlutinans (Foc) is a serious root-invading and xylem-colonizing fungus that causes yellowing in Brassica oleracea. To comprehensively understand the interaction between F. oxysporum and B. oleracea, composition of the xylem sap proteome of the non-infected and Foc-infected plants was investigated in both resistant and susceptible cultivars using liquid chromatography-tandem mass spectrometry (LC-MS/MS) after in-solution digestion of xylem sap proteins. Whole genome sequencing of Foc was carried out and generated a predicted Foc protein database. The predicted Foc protein database was then combined with the public B. oleracea and B. rapa protein databases downloaded from Uniprot and used for protein identification. About 200 plant proteins were identified in the xylem sap of susceptible and resistant plants. Comparison between the non-infected and Foc-infected samples revealed that Foc infection causes changes to the protein composition in B. oleracea xylem sap where repressed proteins accounted for a greater proportion than those of induced in both the susceptible and resistant reactions. The analysis on the proteins with concentration change >=2 fold indicated a large portion of up- and down-regulated proteins were those acting on carbohydrates. Proteins with leucine-rich repeats and legume lectin domains were mainly induced in both resistant and susceptible system, so was the case of thaumatins. Twenty-five Foc proteins were identified in the infected xylem sap and ten of them were cysteine-containing secreted small proteins that are good candidates for virulence and/or avirulence effectors. The findings of differential response of protein contents in the xylem sap between the non-infected and Foc-infected samples as well as the Foc candidate effectors secreted in xylem provide valuable insights into B. oleracea-Foc interactions.